Digital Marketing, Brand Trust, and Generation Z Consumers’ Decision to Use LinkAja E-Wallet in Mataram, Indonesia - Fetrige Zenisa Wibowo; Emilia Septiani (Future Techno-Science, 2026)
This study investigates the extent to which digital marketing and brand trust shape Generation Z consumers’ decisions to use the LinkAja e-wallet in Mataram, Indonesia. Although digital wallets have become increasingly embedded in youth payment practices, platform-specific adoption remains uneven, indicating the need to examine how promotional communication and trust-based perceptions operate in a local urban context. A causal-associative quantitative design was employed using survey data from 100 purposively selected Generation Z respondents who were 18–29 years old, lived or conducted activities in Mataram, and had used LinkAja within the previous six months. Data were collected using a structured Likert-scale questionnaire and analyzed through descriptive statistics and multiple linear regression. The results show that digital marketing has a positive and significant effect on the decision to use LinkAja (B = 0.545; beta = 0.533; p = 0.006), whereas brand trust has a positive but statistically non-significant effect (B = 0.319; beta = 0.302; p = 0.114). Simultaneously, digital marketing and brand trust significantly explain consumers’ usage decisions, F(2,97) = 103.797, p < 0.001, with an adjusted R2 of 0.675. The study contributes to digital consumer behavior literature by showing that, for Generation Z users in Mataram, informative and accessible digital marketing is more decisive than brand trust in explaining LinkAja usage. However, the high variance inflation factor indicates that partial effects should be interpreted cautiously. The findings suggest that e-wallet providers should integrate promotional attractiveness with credible security communication, transparent service information, and user-oriented digital engagement.